Technology use and reading comprehension among Australian Indigenous adolescents - Johnson, Genevieve (TI Journals, 2013)
Recent advances in broadband and mobile phone access have resulted in increased use of information, communicaiton and entertainment technologies by Indigenous Australians in remote regions of Australia. Twenty-three Indigenous adolescents (mean age 16.4 years) residing in remote regions of Western Australia participated in individual structured interviews which queried age of first use and current frequency of use of television, computers, the internet, video games and moble phones. A cloze deletion procedure was also individually administered to measure reading comprehension. Although age of first use of devices evidenced considerable variability, there were no significant relationships to reading comprehension. However, as frequency of current mobile phone use increased, reading comprehesnion tended to increase and as frequency of current computer use increased, reading comprehension tended to decrease. Mobile phones, commonly used to text message, may facilitate reading achievement among adolescents characterised by limited literacy skills in Standard English.